ISSUES OF DEVELOPING A MODERN COMPETENCY-BASED MODEL IN THE SYSTEM OF TRAINING FINE ARTS TEACHERS - Shovdirov Sunnat Aslanovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the theoretical and practical issues involved in developing a modern competency-based model for the training of fine arts teachers. The rapid changes in education, technology, and society have transformed the requirements for teacher professionalism, making it necessary to adopt new approaches to pedagogical design and teacher preparation. A competency-based model focuses on integrating knowledge, skills, values, and personal qualities that enable teachers to effectively respond to contemporary educational challenges. In fine arts education, such a model emphasizes creative thinking, cultural awareness, digital literacy, and the ability to foster students’ aesthetic and emotional development. The paper analyzes the structure of teacher competencies, discusses methodological principles for their formation, and identifies pedagogical conditions necessary for implementing a competency-based approach in the higher education system. The study concludes that creating a modern competency-based model for fine arts teacher training is a crucial step toward improving the quality of art education and ensuring its relevance to the demands of the 21st century.